Synergistic Anti-Tumor Activity by Targeting Multiple Signaling Pathways in Ovarian Cancer - Wei Wen (Cancers, 2020)
More effective therapy is needed to improve the survival of patients with advanced and recurrent ovarian cancer. Preclinical and early clinical studies with single molecular targeted agents have shown limited antitumor activity in ovarian cancer, likely due to compensation by alternative growth/survival pathways. An emerging strategy in overcoming resistance is to combine inhibitors targeting multiple pathways. In this study, we used a novel strategy of combining several FDA-approved targeted drugs, including sunitinib, dasatinib, and everolimus, in human ovarian cancers. Combination of the tyrosine kinase inhibitor sunitinib with the SRC inhibitor dasatinib showed synergistic anti-tumor activity in human ovarian cancer cells. The increased activity was associated with inhibition of the STAT3, SRC, and MAPK signaling pathways, but not AKT signaling. To inhibit the PI3K/AKT/mTOR pathway, we added the mTOR inhibitor everolimus, which further increased anti-tumor activity in cells. Combined treatment with sunitinib, dasatinib, and everolimus also resulted in greater inhibition of human ovarian tumor growth in mice. Furthermore, the triple combination also synergistically increased the anti-tumor activity of paclitaxel, both in vitro and in vivo. Taken together, our results demonstrate that simultaneous inhibition of several signaling pathways results in better anti-tumor activity compared to inhibiting any of these signaling pathways alone.